2019
DOI: 10.1063/1.5094907
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of benzene, naphthalene, and azulene with alkali-metal and alkaline-earth-metal atoms for ultracold studies

Abstract: We consider collisional properties of polyatomic aromatic hydrocarbon molecules immersed into ultracold atomic gases and investigate intermolecular interactions of exemplary benzene, naphthalene, and azulene with alkali-metal (Li, Na, K, Rb, Cs) and alkaline-earth-metal (Mg, Ca, Sr, Ba) atoms. We apply the stateof-the-art ab initio techniques to compute the potential energy surfaces (PESs). We use the coupled cluster method restricted to single, double, and noniterative triple excitations to reproduce the corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 115 publications
0
11
1
Order By: Relevance
“…In addition to crystalline organic semiconductor materials derived from the acene family of molecules discussed herein, covalently linked dimers are also conceivable as suitable candidate systems. Anticipating further progress in cooling of polyatomic molecules with lasers or other techniques for obtained cold polyatomic molecules, one might also envision molecules stored in optical lattices, in which intermolecular interactions can specifically be tailored, as potential probes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to crystalline organic semiconductor materials derived from the acene family of molecules discussed herein, covalently linked dimers are also conceivable as suitable candidate systems. Anticipating further progress in cooling of polyatomic molecules with lasers or other techniques for obtained cold polyatomic molecules, one might also envision molecules stored in optical lattices, in which intermolecular interactions can specifically be tailored, as potential probes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…24 There are several previous studies of alkali metal ions interacting with benzene, as they form a prototypical system that is sensitive to polarization and dispersion of the benzene p electron cloud. [25][26][27] In particular, a recent study by Savarese et al compared a range of computational methods and dispersion corrections on Li + -benzene complexes and showed that for some methods, such as DFT B3LYP, the inclusion of an empirical dispersion correction resulted in qualitative and quantitative differences from the reference CCSD(T) complete basis set (CBS) 28 limit. 29 This result prompted us to study the M + -benzene (Bz) complex using computational methods capable of being extended to the large nanohoop cavities.…”
Section: Computational Details and Methodsmentioning
confidence: 99%
“…[ 15–17 ] The reaction of aromatic hydrocarbons with alkali metals has long been recognized to yield aromatic radical anions. [ 18,19 ] These radical anions are usually short‐lived reactive intermediates that are synthetically useful in a variety of organic and organometallic reactions as strong reductants. [ 20–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The reaction of aromatic hydrocarbons with alkali metals has long been recognized to yield aromatic radical anions. [18,19] These radical anions are usually short-lived reactive intermediates that are synthetically useful in a variety of organic and organometallic reactions as strong reductants. [20][21][22] Benzophenone in its lowest excited state plays an important role in a variety of photochemical reactions and is known to be highly electrophilic.…”
Section: Introductionmentioning
confidence: 99%